Implementation of Early Childhood Discipline Character Education at Ra Al Amin Jakarta - Elin Herlina; Hapsa Kamaruddin (Cv. Kayaswara, Indonesia, 2025)
This study aims to determine the implementation of disciplinary character education in early childhood at RA Al Amin Jakarta, and to identify its influence on children's character development. Disciplinary character education in early childhood is one of the important aspects in forming positive behavior that can support children's development both in the family and school environment. The research method used is qualitative descriptive research with a case study approach. Data were collected through observation, interviews with teachers, principals, and parents, as well as document analysis related to the implementation of character education in schools. The results of the study indicate that the implementation of disciplinary character education at RA Al Amin Jakarta has been running well through various activities that support disciplinary values, such as the formation of punctual habits, arranging daily routines, and strengthening discipline in various activities. Teachers also play an active role in instilling discipline through role models and consistent approaches. Children show positive behavioral changes, such as increased discipline in following existing schedules and rules. The implication of this study is the importance of the role of schools and parents in supporting disciplinary character education to form children who have structured and independent behavior. The application of the results of this study can be used as a guideline for other early childhood education institutions in implementing disciplined character education effectively and in a planned manner, as well as a reference for improving collaboration between schools and parents in educating children.